PERBEDAAN KEMANDIRIAN ANTARA ANAK SULUNG DAN ANAK BUNGSU PADA SISWA TK. AL-DJUFRI III DESA BLUMBUNGAN KECAMATAN LARANGAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Farihah Farihah; M Ridlwan; Ratno Abidin (PROCEEDING UMSURABAYA, 2022)
The purpose of this study was to determine the difference in independence between the eldest and youngest children in Al-Djufri III Kindergarten students in Blumbungan Village, Larangan District, Pamekasan Regency, in the 2021/2022 Academic Year. The influence of family on adolescent independence is related to the role of parents. In this case the father and mother have a real role. Not only independence, parenting can also determine the child's mindset. The family environment plays an important role in instilling values in a teenager, including the value of independence. This research method uses quantitative methods with correlational data analysis techniques. The purpose of using correlational statistical analysis is to obtain an overview of the relationship between children's independence based on the three parenting styles of parents, namely democratic, permissive and authoritarian parenting. The results of the research that has been done turns out that there are differences in independence between the eldest and youngest children in kindergarten students. Al- Djufri III Blumbungan Village, Larangan District, Pamekasan Regency, 2021/2022 Academic Year. The eldest children tend to be more independent than the youngest children.Keywords: teenager; eldest child; correlational; statistics